2022
DOI: 10.3224/dms.v15i1.09
|View full text |Cite
|
Sign up to set email alerts
|

Trust in times of crisis: opportunities and pitfalls of cooperation between volunteers and local governments

Abstract: During the so-called refugee crisis of 2015/16 an estimated 25% of the German population was actively engaged as volunteers. Volunteers thus constitute a group of citizens who are high stake actors in crisis management due to their personal experience and direct interaction with the local public administration. This paper scrutinizes how the interaction between volunteers and local administrations in crisis management affects volunteers’ trust in the local public administration. Following the literature on adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Citizens' involvement into decision-making processes for public services is one of the ways to achieve the goal. According to social capital research and stakeholder interaction theory, volunteering and civic engagement in general also promotes social trust in public institutions (Lenz, 2022). Here, co-creation can serve as a form of collaboration between the public administration organizations and its stakeholders for a more efficient and better-quality public service delivery (Puksas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Citizens' involvement into decision-making processes for public services is one of the ways to achieve the goal. According to social capital research and stakeholder interaction theory, volunteering and civic engagement in general also promotes social trust in public institutions (Lenz, 2022). Here, co-creation can serve as a form of collaboration between the public administration organizations and its stakeholders for a more efficient and better-quality public service delivery (Puksas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Trust in government is an important factor influencing citizens' involvement in co-creation of public services. Trust in institutions is a key element in the functioning of democratic systems and influences citizens' political behaviour (Lenz, 2022). Scholars exploring the links between welfare conditionality and co-creation have found that distrust of the public system and citizens is an obstacle to co-creation (Larsen & Caswell, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation